2008
DOI: 10.1088/0022-3727/41/20/205418
|View full text |Cite
|
Sign up to set email alerts
|

Filament discharge enhances field emission properties by making twisted carbon nanofibres stand up

Abstract: Abstract. Twisted carbon nanofibers, named carbon nanotwists (CNTws), in a flocculated form were pasted, printed on the conductive silicon substrate, and then treated by dielectric barrier discharge using He and N 2 gases. Vertically upright nanofibers were clearly obtained by "filament discharge mode" in N 2 gas. As the treating time increased up to ~60 s, the height of the nanofiber tips became uniform. Consequently, the field emission property was greatly enhanced and showed a threshold electric field of 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In addition, the coil diameter of columnar CNCs was smaller than that of the MWCNCs, indicating that the form of columnar CNCs resembles that of CNTw. (Hosokawa et al, 2008), (Yokota et al, 2010), (Takikawa et al, 2000) To our knowledge, the columnar CNCs have not been previously reported though there are reports of MWCNCs. (Kanada et al, 2008), (Lu et al, 2004), (Yang et al, 2003) Fig.…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, the coil diameter of columnar CNCs was smaller than that of the MWCNCs, indicating that the form of columnar CNCs resembles that of CNTw. (Hosokawa et al, 2008), (Yokota et al, 2010), (Takikawa et al, 2000) To our knowledge, the columnar CNCs have not been previously reported though there are reports of MWCNCs. (Kanada et al, 2008), (Lu et al, 2004), (Yang et al, 2003) Fig.…”
Section: Methodsmentioning
confidence: 88%
“…The field emission property was enhanced by the upright CNTws. (Hosokawa et al, 2008) The detail of experimental conditions is indicated in each of the figure caption.…”
Section: Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…They are also used in nanosprings [26][27][28][29][30], electrode materials in fuel cells [31][32][33][34], field emitters [35][36][37], magnetic sensors [38,39], and various industrial fields [40][41][42].…”
Section: Catalystmentioning
confidence: 99%